Social control and its relationship with the Psycology capital cogitation of kindergartens departments female students (Journal of the College of Basic Education, 2020)
Targeting current search know exactly the kindergarten Department students social and psychological capital known students kindergarten Department, know the exact relationship between the social and relational capital among students kindergarten Department. Search sample consisted of (100) freshman of the kindergarten Department students for the academic year 2018-2019, the researcher has build exact scale scale building social capital and applied the scales on students kindergarten Department, then handled data using the Pearson correlation coefficient to find plants The relationship between reliability and link social control and psychological capital, as one researcher sample t-test is used to find the significance of the difference between the arithmetic mean and the sample mean of two variables, the search results have come to: kindergarten students with social settings. The kindergarten students with Psycology capital cogitation. There is a positive correlation between social control and psychological capital.